Peranan Psikologi Olahraga Terhadap Pencapaian Prestasi Tingkat Nasional Atlet Pelatda Judo DKI Jakarta di Masa Pandemi Covid-19 - Ray Rexy Aprima Idra; Ahmad Muchlisin Natas Pasaribu; Juli Candra (Universitas Singaperbangsa, 2021)
The purpose of the study was to describe descriptively the role of psychology in the achievement of national level achievements of DKI Jakarta regional judo athletes during the covid-19 pandemic. The research method used in this research is descriptive qualitative where the data is in the form of words that are described. Data retrieval was carried out using a google form questionnaire which was distributed to all athletes of the DKI Jakarta judo training center. This research was conducted at Dojo Jumantoro which is located in Pandasari, Kec. Ciawi, Kab. Bogor, West Java. in this study managed to get 17 respondents which consisted of 9 women and 8 men. In this study, the results obtained 7 aspects that greatly affect the psychology of athletes, namely emotional aspects, aggressive aspects, motivational aspects, intelligence aspects, self-confidence aspects, anxiety aspects, and discipline aspects